A rare case of mucinous tubular and spindle cell renal cell carcinoma with sarcomatoid change (Indian Journal of Case Reports, 2018)
Mucinous tubular and spindle cell renal cell carcinoma is a rare and recently described subtype of RCC. We present the case of a 45-year-old woman with incidentally detected left renal mass. Imaging revealed a large mass and left radical nephrectomy was performed, histopathology revealed it to be a mucinous tubular and spindle cell carcinoma with sarcomatoid change. She is under close follow-up for the last 6 months.